Role of L-carnitine in the prevention of acute liver damage induced by carbon tetrachloride in rats - Demirdag, K; Bahcecioglu, IH; Ozercan, IH; Özden, M; Yilmaz, S; Kalkan, A (Wiley, 2004)
Background and Aim: Lipid peroxidation is the most important mechanism in the pathogenesis of acute liver damage with carbon tetrachloride (CCl4). L-carnitine may prevent lipid peroxidation and thus may protect against liver damage. In the present study we investigated the protective effect of L-carnitine in experimental acute liver damage induced by CCl4. Methods: Fifty rats were allocated to five equal groups. The first group was the control (group 1), the second group received an intraperitoneal CCl4 injection for 3 days (group 2), and the third group received a 50 mg/kg subcutaneous L-carnitine injection for 4 days, beginning a day before CCl4 injection. The CCl4 injection was continued for 3 days in the concerned group (group 3). Group 4 was given a CCl4 injection for 7 days and group 5 received a 50 mg/kg subcutaneous L-carnitine injection for 8 days, beginning a day before CCl4 injection. This group continued to receive a CCl4 injection for 7 days. Rats in groups 2 and 3 were killed on the fifth day. Rats in groups 1, 4 and 5 were killed on the ninth day. Plasma and liver tissue malondialdehyde (MDA) levels, glutathione peroxidase (GSH-Px) activity and liver enzyme levels were studied. Histopathological investigations were conducted. Results: Liver tissue MDA levels decreased significantly in group 3 compared to group 2 (P<0.001). Liver tissue MDA levels in group 5 decreased significantly in comparison to those of group 4 (P<0.001). Liver tissue GSH-Px activity in group 5 was significantly lower than that in group 4 (P<0.05). There were no significant differences between groups 3 and 4 regarding GSH-Px activity (P>0.05). Steatosis, inflammation and necrosis in group 3 were significantly reduced when compared to group 2 (P<0.01). Fibrosis development was not identified in groups 2 and 3. Steatosis in group 5 was significantly lower than that in group 4 (P<0.05) and there were no significant differences between groups 4 and 5 with regards to inflammation and necrosis (P>0.05). Mild fibrosis development was identified in groups 4 and 5 but the difference between the groups was not significant. Conclusions: It appears that L-carnitine has a protective effect in the early stage of experimental acute liver damage induced by CCl4. As the toxic effect or damage continues, its effect lessens. (C) 2004 Blackwell Publishing Asia Pty Ltd.
Keywords: acute liver damage; carbon tetrachloride; L-carnitine; lipid peroxidation